ANALYSIS OF WORK DISCIPLINE, SUPERVISION, AND TEAM COOPERATION IN RELATION TO EMPLOYEE PERFORMANCE AT THE ENVIRONMENTAL SERVICES DEPARTMENT OF PALEMBANG - Calvin, Venny Anggarda; Tien Yustini; Siti Komariah Hildayanti (Magister Manajemen Universitas Islam Malang, 2024)
This study examines the influence of work discipline, supervision, and teamwork on employee performance at the Environmental Service Office of Palembang City. This topic is important as employee performance directly affects the quality of public services. The research uses a descriptive quantitative approach with 65 respondents selected through a saturated sampling technique. Data were analyzed using multiple linear regression.The results show that work discipline, supervision, and teamwork have a positive and significant effect on employee performance, both partially and simultaneously. These findings indicate that strengthening these factors can improve organizational performance. This study contributes to the development of performance improvement strategies through organizational behavior approaches in the public sector.